2015
DOI: 10.5897/jma2014.0334
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial activity of endophytic fungi isolated and identified from salt marsh plant in Vellar Estuary

Abstract: The purpose of this work was to evaluate the antimicrobial potential of endophytic fungi isolated from leaves and stems of Suaeda maritima and Suaeda monoica. Many endophytes were isolated by using potato dextrose agar (PDA) medium. All the endophytic isolates were identified by using standard taxonomic keys and monographs. From a total of 16 isolates, nine potent strains were taken for further study. The fungal culture was extracted with ethyl acetate and used as a crude extract for checking antimicrobial act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(8 citation statements)
references
References 35 publications
(26 reference statements)
1
3
0
1
Order By: Relevance
“…This could be linked to a synergistic or additive effect of the secondary metabolites present in the methanolic extract. In addition, the mean bactericidal effect of this extract on the strains tested is in line with data reported by Amadi and Adeniyi, as well as those reported by Indira et al [ 59 , 60 ] who demonstrated the antimicrobial activity of the genus Aspergillus . The reduction mechanisms of bacteria or fungi growth of the Aspergillus genus ( Aspergillus terreus , Aspergillus flavus , and Aspergillus fumigatus ) endophytes may possess higher concentration of alkaloids (fumiclavin A and B and, fumigaclavin B).…”
Section: Discussionsupporting
confidence: 91%
“…This could be linked to a synergistic or additive effect of the secondary metabolites present in the methanolic extract. In addition, the mean bactericidal effect of this extract on the strains tested is in line with data reported by Amadi and Adeniyi, as well as those reported by Indira et al [ 59 , 60 ] who demonstrated the antimicrobial activity of the genus Aspergillus . The reduction mechanisms of bacteria or fungi growth of the Aspergillus genus ( Aspergillus terreus , Aspergillus flavus , and Aspergillus fumigatus ) endophytes may possess higher concentration of alkaloids (fumiclavin A and B and, fumigaclavin B).…”
Section: Discussionsupporting
confidence: 91%
“…Despite extensive work on fungal endophytehalophyte systems (e.g. Bilal et al 2018;Gopi and Jayaprakashvel 2017;Indira et al 2015;Khalmuratova et al 2015;Maciá-Vicente et al 2012;Sun et al 2011a, b), there is limited information on the properties of endophytic fungi from saline habitats and how they contribute to improving the plant performance. Consequently, in this study we investigated a salt-accumulating halophyte, Salicornia europaea L. (family Amaranthaceae), which is one of the most salt tolerant halophytes in the world (Nikalje et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The roots and twigs' samples were sliced longitudinally while others were cut into more or less forms and placed into media (PDA + chloramphenicol, LB-agar), containing Petri dishes so that the freshly cut edges were in direct contact with the agar surface. To check for the efficiency of the procedure, 0.1 ml of the final rinsing water was inoculated on LB-agar, PDA + chloramphenicol, and incubated under the same conditions as the samples (16,(42)(43)(44)(45)(46)(47).…”
Section: Materials and Methods Isolation And Purification Procedures Cmentioning
confidence: 99%